BAHASA TUBUH: TANDA DALAM SISTEM KOMUNIKASI - Hidayat, Arif (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2010)
Body language as a system of marking and communications to create action, require more interpretation forthe purpose can be achieved. From the standpoint of semiotic and communicative action, every communicationreceived by others, then there will be certain impacts that occur, depending on the power of interpretation. Making of thesemiotics of body language and focus on how the message being abstracted by the receiver. Body language as amessage with a set of symbols that can be verbal communication, can not be understood properly without any expressionthat is formed based on mythology. The existence of this mythology helps to understand the body language in the realm ofa specific code that has been universally believed.